Inventory control practices - Mohammad Hafiz, b. Hj. Amran (Faculty of Engineering, 2006)
Manufacturer's nowadays are competing very competitively among them self. This is to gain the total maximum profit and minimize loss. the objective of this study is to determine the factors that causing poor inventory control practice, the effect of the poor inventory control practice to the company performance or system and lastly the approach for a good inventory control practices.